Butterflies of Athgarh Forest Division, Odisha, Eastern India, with notes on some significant records - Payra, Arajush; K. Dash, Suraj; P. Das, Udit; S. Palei, Himanshu; K. Mishra, Arun (Acta Biologica Sibirica, 2019)
The present paper deals with first annotated list of butterflies from Athgarh Forest Division, Odisha, India. 136 species belongs to six families were recorded during January 2015 to September 2015. Notes on some of the significant record of butterflies for the region, were provided along with their distribution. Among the recorded 136 species of butterflies, 14 species are legally protected under Indian Wildlife Protection Act, 1972.